Influence of Water-Resisting Layer Thickness on Fracture Evolution in Karst Tunnel and Control Measures. (8th March 2022) - Liu, Chun; Jiang, Congying
Abstract : In this paper, a series of studies are carried out on the hidden karst encountered in the excavation of Baziling tunnel. In this paper, the safe thickness of the water-resisting layer in a hidden karst cave and tunnel is studied by means of engineering geological investigation, numerical simulation, and neural network. The numerical calculation model is established through the geological survey. Innovate to use BP neural network and differentiation algorithm to inverse the rock mechanical parameters. By analyzing the influence of different thicknesses of the water-resisting layer on the deformation and failure of surrounding rock, the final thickness of the water-resisting layer is obtained. At the same time, the influence of water pressure on the thickness of the water-resisting layer is studied, and the treatment scheme under different water pressure is finally determined.